Indigeneous Streptomyces spp. isolated from Cyperus rotundus rhizosphere indicate high mercuric reductase activity as a pontential bioremediation agent - Hanum Mukti Rahayu; Wahyu Aristyaning Putri; Anis Uswatun Khasanah; LANGKAH SEMBIRING; Yekti Asih Purwestri (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rahayu HM, Putri WA, Khasanah AU, Sembiring L, Purwestri YA. 2021. Indigenous Streptomyces spp. isolated from Cyperus rotundus rhizosphere indicate high mercuric reductase activity as a potential bioremediation agent. Biodiversitas 22: 1519-1526. The purification and characterization of mercuric reductase of four indigenous Streptomyces spp. from Cyperus rotundus L. rhizosphere in mercury-contaminated area have been investigated. Cell-free extract was obtained by disrupting cells using sea sand at 4 °C followed by centrifugation. Mercuric reductase was purified by ammonium sulfate precipitation, dialysis, and chromatography column (DEAE Sepharose anion column chromatography). The determination of optimum pH and temperature of mercuric reductase activity was measured based on the number of NADPH2 oxidized to NADP per mg protein per minute using a spectrophotometer. The molecular weight of mercuric reductase was determined using SDS-PAGE. Result showed that the highest specific activity of mercuric reductase was recorded from Streptomyces spp. BR28. The optimum pH and temperature of cell-free extract enzyme mercuric reductase were 7.5 and 80 °C, respectively. The enzyme was purified to 431.87-fold with specific activity 21918.95 U/mg protein. SDS PAGE showed that the molecular weight of mercuric reductase in Streptomyces spp. BR 28  ranged from 50 kDa to 75 kDa. It can be concluded that Streptomyces isolates contain mercuric reductase and have potential as mercury bioremediation agent to overcome mercury contamination in the environment.